2011
DOI: 10.1371/journal.pgen.1002145
|View full text |Cite
|
Sign up to set email alerts
|

Foxp2 Regulates Gene Networks Implicated in Neurite Outgrowth in the Developing Brain

Abstract: Forkhead-box protein P2 is a transcription factor that has been associated with intriguing aspects of cognitive function in humans, non-human mammals, and song-learning birds. Heterozygous mutations of the human FOXP2 gene cause a monogenic speech and language disorder. Reduced functional dosage of the mouse version (Foxp2) causes deficient cortico-striatal synaptic plasticity and impairs motor-skill learning. Moreover, the songbird orthologue appears critically important for vocal learning. Across diverse ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
329
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(353 citation statements)
references
References 69 publications
23
329
1
Order By: Relevance
“…We also studied FOXP2 interactions using STRING [36,37] (Figure 3a), BioGRID [38] and IntAct [64]. For a more extensive study, we referred scientific literature [60][61][62][63][64][65][66][67][68][69] and took into consideration some genes that were not common targets but play important roles in the nervous system or in pathogenesis of neurological disorders (for example, CNTNAP2 and BDNF) and showed potential in being indirectly co-regulated by FOXP2 and miR-3666 through common target genes. Therefore, a total of 30 genes were selected for developing our models (Supplementary Table S4).…”
Section: Four Models Developed Show Mechanisms By Which Mir-3666 Mighmentioning
confidence: 99%
“…We also studied FOXP2 interactions using STRING [36,37] (Figure 3a), BioGRID [38] and IntAct [64]. For a more extensive study, we referred scientific literature [60][61][62][63][64][65][66][67][68][69] and took into consideration some genes that were not common targets but play important roles in the nervous system or in pathogenesis of neurological disorders (for example, CNTNAP2 and BDNF) and showed potential in being indirectly co-regulated by FOXP2 and miR-3666 through common target genes. Therefore, a total of 30 genes were selected for developing our models (Supplementary Table S4).…”
Section: Four Models Developed Show Mechanisms By Which Mir-3666 Mighmentioning
confidence: 99%
“…However, given that it is a transcription factor, genes regulated by FOXP2 could have roles in other forms of language disorder. Several studies have together identified thousands of genes that are potentially regulated by FOXP2 in at least one tissue or developmental timepoint Vernes et al 2007Vernes et al , 2011Konopka et al 2009). One early study (Vernes et al 2008) chose to follow up specifically on CNTNAP2, which encodes a neuronal cell-surface transmembrane protein.…”
Section: Stutteringmentioning
confidence: 99%
“…Several studies have therefore attempted to identify such neural targets. However, there is limited overlap between datasets, and the crucial targets of FOXP2 with regard to language disorder remain unclear Vernes et al 2007;Vernes et al 2011;Konopka et al 2009). One key set of FOXP2 targets may be those involved in neurite outgrowth.…”
Section: Epilepsy-aphasia Spectrum Disordersmentioning
confidence: 99%
See 2 more Smart Citations